Methodology For Using NonStandard Tasks In The Development Of Thinking Of Future Engineers - Baratov Joʻraqoʻzi Shukurjon oʻgʻli (Genius Journals, 2025)
In this article, the use of non-standard tasks based on an integrative approach in the training of future engineers allows for the development of thinking and logical thinking, the development of knowledge, skills, abilities, and competencies of future engineers, creative thinking, the ability to understand, explain, and develop the rapidly developing technologies of today and the present in a dynamic environment by the European model is one of the pressing issues of today. The improvement of the methodology for applying non-standard tasks based on an integrative approach to practice and a theoretical approach to the relationship between pedagogical education and training of future engineers is envisaged.
Keywords: logical thinking; the concept of a non-standard task